PENERAPAN METODE TAGUCHI UNTUK KASUS MULTIRESPON MENGGUNAKAN PENDEKATAN GREY RELATIONAL ANALYSIS DAN PRINCIPAL COMPONENT ANALYSIS (Studi Kasus Proses Freis Komposit GFRP) - Annisa Ayu Wulandari; Triastuti Wuryandari; Dwi Ispriyanti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Taguchi method is a method for quality control of product by off line. Taguchi method usually used to solve optimization problem with single respon. Multirespon case was done by using Grey Relational Analyisis (GRA) and Principal Component Analysis (PCA). With GRA method is obtained many Grey Relational Grade value. For weight is estimated using PCA. The case study use freis process GFRP composite with characteristic smaller is better. From the research is obtained combination in optimal canditions for factor fiber orientation angle at 150, helix angle at 250, and feed rate at 0,04 mm/rev. While the respon that observed are surface roughness, machine force, and delamination factor. The value of contribution percentage for each factor is 69,596% for fiber orientation angle, 9,768% for helix angle and 11,9841% for feed rate..Keywords : Multirespon Optimization, Taguchi Method, Grey Relational Analysis, Principal Component Analysis, Freis Process GFRP Composite